Design, Manufacturing, and Testing of Radial Conduction Test Device - SUYATNO, CHRISTIAN
Heat transfer has been applied in many different engineering fields and used in designing engineering tools. Therefore, it is important for engineering students to understand heat transfer. Students will understand better if they can see, test, and analyze the phenomenon directly compared to just reading the literature. The need to get a good device to study heat transfer is the basis for this final project. The science of heat transfer is divided into three major parts; namely heat conduction, convection, and radiation. This final project concentrates in showing the phenomenon of radial conduction. The approach used in this final project are as follows: to design the test rig by first simulating in the Fluent software, manufacture the device, perform trial testing, and analyze test results. Preliminary results are obtained in the form of temperature distribution in the radial direction of the test specimen. Based on this, the thermal conductivity of the test specimen may be calculated. The theoretical thermal conductivity of the steel specimen is 60.5 W/mK. The thermal conductivity obtained from the experiment is 20.4 W/mK. Upon further evaluation, we may conclude that the discrepancy originates from thermal losses in the system. However, the test result is still in the same order of magnitude as the theoretical ones. Hence, we may conclude that the prototype performs well, but requires further refinement.